2019
DOI: 10.1097/fpc.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Analytical validity of a genotyping assay for use with personalized antihypertensive and chronic kidney disease therapy

Abstract: Hypertension and chronic kidney disease are inextricably linked. Hypertension is a well-recognized contributor to chronic kidney disease progression and, in turn, renal disease potentiates hypertension. A generalized approach to drug selection and dosage has not proven effective in managing these conditions, in part, because patients with heterogeneous kidney disease and hypertension etiologies are frequently grouped according to functional or severity classifications. Genetic testing may serve as an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…At present, there are many ways to treat CKD, including hypoglycemic [15], antihypertensive [16, 17], and control of urinary protein [18]. However, the treatment cost is high [19], the side effects are obvious [20], and the therapy is long-lasting [21] and ineffective [22].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many ways to treat CKD, including hypoglycemic [15], antihypertensive [16, 17], and control of urinary protein [18]. However, the treatment cost is high [19], the side effects are obvious [20], and the therapy is long-lasting [21] and ineffective [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among the three studies assessed in this review with a phenotype-genotype concordance of less than 70%, one observed no separation in the distribution of its caffeine phenotyping results and the other two included the *12 and *13 variants [37, 44, 45]. As a result, our approach has been to adopt the 4-SNP model proposed by Hein et al [8, 33]. This 4-SNP model includes the *5, *6, *7, and *14 alleles and shows equivalent NAT2 phenotyping concordance (98.4%) compared to a 7-SNP model (98.4%) with the *11, *12, and *13 alleles included [33].…”
Section: Concordance Between Nat2 Phenotype and Genotypementioning
confidence: 99%
“…However, it is still commonly used in resistant hypertension and as a first-line therapy for afterload reduction in African Americans with heart failure [7]. In the Indiana University Healthcare system, NAT2 genotyping has been performed clinically as part of an antihypertensive pharmacogenetics panel since 2017, with results available to the clinician in the electronic health record [8, 9]. Among the 580 individuals who received antihypertensive pharmacogenetic testing in a kidney clinic, 13% of all renal patients were prescribed hydralazine (alone or in combination with isosorbide dinitrate), including 25% of all African Americans.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that embedding a panel of pharmacogenomic predictors of antihypertensive response in routine clinical practice would aid patients and practitioners in arriving at an efficacious blood pressure regimen, either by identifying less efficacious medications in an individual’s current regimen or selecting an efficacious drug as the “next” antihypertensive agent. To facilitate this, a clinical genotyping assay was developed and implemented across multiple health systems, with results and recommendations recorded in the electronic health records (EHR) for 40 variants and 11 drug-gene pairs relevant to hypertension control 14 .…”
Section: Introductionmentioning
confidence: 99%